Кріорезистентність та індекс висоти заморожених ягід суниці за попередньої обробки в розчинах зі структуроутримуючими властивостями - Заморська, Ірина Леонідівна (НТУ "ХПІ", 2017)
Досліджено кріорезистентність, індекс висоти та втрати маси заморожених ягід суниці залежно від попередньої обробки в розчинах зі структуроутримуючими властивостями: 1, 2 та 3 %-ного розчину картопляного крохмалю та 1 і 2 %-ного цукрово-пектинових розчинів. Доведено, що попередня обробка ягід суниці перед заморожуванням у розчинах зі структуроутримуючими властивостями сприяла підвищенню їхньої кріорезистентності на 0,4-2,5 %, індексу висоти – до 0,5 %, зниженню втрат маси на 0,9-1,6 %. Встановлено, що межею допустимих втрат маси під час заморожування ягід суниці за яких зберігається висока кріорезистентність та індекс висоти є 2 %.

The purpose of the work is to study the pretreatment effect of strawberries in structure-retentive solutions before freezing on the indicators of cryoresistance and height index. Cryoresistance was determined by the difference of the mass of frozen berries and that of defrosted ones, and it was expressed in percents; height index was expressed in terms of the correlation between the height of defrosted berries and that of fresh berries in percents; height index of fresh strawberries was taken as 100%. It was established that the treatment of strawberries in structure-retentive solutions before freezing favored the increase of their cryoresistance by 0,4-2,5 %, compared with the control. The berries which were pretreated in 2 % sugar-pectin solution had much higher cryoresistance, namely 98,3 %. Cryoresistance gradually decreased during the storage of frozen strawberries. Freezing of strawberries resulted in their height ranging from to 96,6 (the control) to 97,1 % when berries were treated with 3 % starch solution. Berry treatment with 1 % sugar-pectin solution did not favor the preservation of a berry form. Height index of strawberry samples did not change after 6 months of their storage. While freezing strawberries their mass losses appeared to be at the level of 2-3,6 % of the initial mass. Pretreatment of berries in structure-retentive solutions made it possible to decrease berry mass by 0,9-1,6 %. Direct average correlative connection (r=0,61±0,05) was established between mass losses and cryoresistance, r=0,52±0,06 was between mass losses and height index 2 % sugar-pectin solution appeared to be very efficient for pretreatment of berries before freezing. A limit level of strawberry mass losses during freezing, when high cryoresistance and height index are preserved, is 2 %.
Cryoresistance and height index of frozen strawberries pretreated in the solutions with structure-maintaining properties
Keywords: розчин; консервування; пектин; хлорид кальцію; метилстераза пектинова; вакуумування; камедь гуарова; freezing; strawberry; solution; cryoresistance; height index